Effect of transcutaneous electrical nerve stimulation based on wrist-ankle acupuncture theory for pain relief during colonoscopy without anesthesia: a randomized controlled trial - Huang, Xiaonan; Wang, Hao; Shi, Lei; Xu, Lifan; Lv, Can; Song, Wenjuan; Huang, Lele; Yan, Feihu; Shi, Ping; Cai, Mengcheng; Fang, Fanfu (Endoscopy, 2024)
Background Colonoscopy is essential for diagnosing colorectal diseases but can cause pain during the procedure. This study explored the analgesic effects of transcutaneous electrical nerve stimulation based on wrist-ankle acupuncture theory (TENS-WAA) in colonoscopy without anesthesia.Methods This prospective study included 120 participants undergoing colonoscopies without anesthesia. The trial group received low-frequency, high-intensity TENS-WAA adjusted to the maximum tolerable current, while the control group received minimal current. The primary outcome was the retrospective pain score on a visual analog scale (VAS). Secondary outcomes included time, heart rate, and credibility/expectancy questionnaire (CEQ) scores.Results Participants who received TENS-WAA reported significantly lower pain VAS scores than the control group (estimated median difference –1.1, 95%CI –2 to –0.4; P = 0.002). Male participants in the trial group experienced significantly lower pain scores than the control group (mean difference –1.4, 95%CI –2.41 to –0.39; P = 0.008). The trial group showed significantly less variation in heart rates (P<0.001) and higher CEQ scores (P = 0.001) than the control group. No adverse events were reported.Conclusion TENS-WAA effectively reduced pain during colonoscopy without anesthesia, especially in male participants, providing a promising noninvasive analgesic method.